The language sign aŋ in the Kazakh Ancient Epos - Zhakupov, Ж.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The article was written in the framework of a grant research project on «Linguistic and genre study of Kazakh folklore».The genre features of the Kazakh Ancient Epos: ways of reflecting reality, which are realized through linguistic means are defined in the given article. It is possible to identify linguistic units that determine the genre of the ancient epic with the help of linguo-folkloristic approach. So, by giving of history and semantics, having revealed the cognitive value of the language sign aŋ, as a supporting word of the concept, it is proved that the Kazakh Ancient Epos is regarded as one of the manifestations of the world art of the “animal style” in Kazakh oral folk art